IMPLEMENTASI METODE EOQ (ECONOMICAL ORDER QUANTITY) PADA SYSTEM INVENTORY DI PERUSAHAAN X - Khairul ihwan (JURNAL PERANGKAT LUNAK, 2023)
In the industrial world, determining the amount of raw material inventory is an important issue, because raw material inventory has a direct effect on the course of production. Errors in determining inventory can paralyze all production activities, because raw materials are the initial materials or media in the production process. If the raw material inventory is too large compared to the company's needs, it will add to the burden on maintenance and storage costs in the warehouse, as well as the possibility of depreciation and a decrease in the quality of raw materials, so this will greatly affect the cost of raw material inventory. And vice versa, if the inventory is too small it will result in a bottleneck in production. Based on the description above, the researcher conducted research at a workshop company in X city. The object of the study was to calculate the cost of procuring AWS welding wire raw materials at the company using the EOQ method. The results showed that the raw material requirement for AWS welding wire in period 9 could be known economically, namely = 77.9817 kg for AWS welding wire. Purchase frequency for AWS welding wire 11 times. The total cost of TIC supplies in period 9 for AWS welding wire = IDR 7,800.00/Kg. To determine the number of orders and the right time to order is when inventory is at point 34.30099 Kg with a reorder amount of 77.9817 kg for AWS welding wire.